THE PARADIGM OF MATN HADITH CRITICISM AND ITS TRANSFORMATION IN THE MODERN ERA - Siswanto, Darul (ULUL ALBAB Jurnal Studi Islam, 2020)
Hadiths or Prophetic traditions as primary sources after Quran in Islamic teachings are important to examine and criticize in terms of authenticity and contents. This research aims at discovering the paradigm of matn hadith criticism used by hadith scholars by looking at their methodology. It is also an attempt to answer some Orientalist opinions about classical hadith scholars who only focus on the criticism of sanad and ignore the matn criticism. Through the inductive method, it can be said that the paradigm believed by hadith scholars in matn critique is the law of contradiction where it is impossible for two authentic hadiths to oppose each other as well as it is impossible for sahih and daif hadiths to be different (ikhtilÃ¢f). Then this research also tries to discover the form of transformation of the matn hadith criticism in the modern era and that Islamic values are still very relevant in all places and times. This research also shows that there are two forms of transformation, namely internal and external transformation, both of which are driven and influenced by the development and progress of the modern era.